Parotid gland metastasis from prostate cancer. Issue 3 (March 2015) - Hélissey, Carole; Rouanne, Mathieu; Arnaud, Francois-Xavier; Le Moulec, Sylvestre
<x xml:space="preserve">Abstract</x> Metastases of prostate cancer originating from the parotid gland are rare. However, this presentation raises the question of the management of visceral metastasis in castration-resistant prostate cancer. We report the case of an 87-year-old man who presented with a right painless parotid mass in the context of castration-resistant prostate cancer, indicating progression of the disease. He received medical treatment based on docetaxel. Here, we discuss the impact of new hormonotherapies such as enzalutamide and abiraterone acetate, which may be used for the management of these patients.